The Dichotomy of Thumbs-Up Emoji in Online Conversations - Pelila, John Rey Osben; Abenoja, Jayson Ace Kigis; Raymundo, Troy Pangwi (Indonesian Journal of Educational Research and Review, 2024)
Emojis have standard meanings, but their interpretations are not universally agreed upon. This discrepancy becomes evident when determining the appropriate use of the thumbs-up emoji, considering its cultural sensitivity and contextual appropriateness. Therefore, this study aims to analyze both positive and negative interpretations of this emoji in online conversations and identify solutions to address potential misinterpretations. Employing a systematic literature review (SLR), the researcher screened 39 records, considering them for review based on inclusion-exclusion criteria such as having full-text articles published in peer-reviewed journals, written in English, and published between 2013 and 2023. After conducting a thematic analysis, it was revealed that the appropriateness of using the thumbs-up emoji varies depending on cultural and social backgrounds, influencing whether individuals find it acceptable for online conversations. Specifically, four positive interpretations of this emoji are that it is used for approval and acceptance, commendation and recognition, affirmation, encouragement, and a supportive gesture. Additionally, two negative interpretations were revealed: it can be seen as offensive and disrespectful in some cultures and inappropriate to use during a crisis. Despite this dichotomy of the thumbs-up emoji, some solutions emerged to address misunderstandings, such as restricting its usage in serious matters, combining the thumbs-up emoji with other elements, and sending a text message instead. Therefore, it is concluded that while some view this emoji positively, its interpretation differs based on cultural and social backgrounds. Thus, effective communication is not solely about one party adapting to another's preferences; it involves mutual adjustment for a seamless conversation flow.